THE EFFECT OF KAHOOT IN ENHANCING VOCABULARY ACHIEVEMENT AT CAMBRIDGE BASED CURRICULUM - Novitasari, Devi; Yappi, Shierly Novalita (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
This study investigated the effectiveness of Kahoot! based game learning in enhancing vocabulary achievement among third-grade students in a Cambridge-based bilingual school in Sidoarjo, addressing a gap in research on digital game-based learning within this specific educational context. Employing a quasi-experimental pretest-posttest design, the research compared an experimental group using Kahoot! with a control group receiving traditional vocabulary instruction. Vocabulary data, focused on descriptive texts, were collected through tests, and statistical analysis, including ANOVA, try-out validation, and independent t-tests, was conducted using SPSS. The findings revealed a statistically significant improvement in vocabulary achievement for the Kahoot! group (p = 0.025), suggesting that the engaging and interactive nature of digital game-based learning more effectively fosters vocabulary mastery compared to traditional methods. These results also support Kahoot!'s utility as a practical tool for formative assessment, particularly within the Cambridge curriculum framework, and offer valuable insights for educators seeking innovative and engaging vocabulary teaching strategies in bilingual learning environments.